Strategies to Increase Financial Inclusion through Financial Technology - Basrowi, Basrowi (Journal of Islamic Economics Lariba, 2019)
The purpose of this study is to describe the strategy of increasing public financial inclusion through the use of fin-tech finance. The method used is descriptive qualitative. Data is obtained from secondary data sourced from the official website of Indonesian banks, financial service authorities, and the finance ministry from 2015-2018. Data were analyzed using theme analysis of an overview of the development of fin-tech in Indonesia over the past four years, and the benefits of fin-tech in improving financial inclusion in Indonesia. The results of data analysis show that, first, the development of fin-tech in Indonesia has exceeded the needs of fin-tech itself. Secondly, the development of fin-tech has been able to increase the financial inclusion of the community even though it is only very small at 0.8%.